Prediction of severe adverse maternal outcome in women admitted in obstetric ward using physiological and biochemical parameters - Rani, Reena; Meena, Sunita Bai; Yadav, C. P.; Goswami, Deepti; Tripathi, Reva; Rathore, Asmita M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To study physiological and biochemical parameters to predict serious adverse maternal outcomes and to develop risk score using above parameters. Methods: This prospective study was conducted in 500 high risk pregnant women attending tertiary care teaching hospital. We noted physiological and biochemical parameters as soon as they were available .The primary outcome measures was “severe adverse maternal outcome(SAMO)” in form of one or more among mortality, near miss morbidity and ICU admissions. Results: Out-off 500 women, severe adverse maternal outcomes were seen in 158 (31.6%) women. Most common cause of near miss maternal morbidity was hypertensive disease of pregnancy (62.7%) followed by major obstetric hemorrhage (18.9%). There were 33(6.6%) ICU admission, 23 (4.6%) maternal death and 153 (30.6%) near miss maternal morbidity. The most common cause of maternal death in our study was obstetric hemorrhage. The significant variables after multivariate analysis [temp, pulse, urine protein] were used to devise a Maternal early warning score (MEWS) based on physiological parameters at score value of ≥1/6 was found to have sensitivity of 70% and specificity of 82% in predicting SAMO with AUROC of 0.76. The significant laboratory parameters after multivariate analysis were blood urea, serum creatinine, serum bilirubin and liver enzymes. The obstetric risk score (Maternal risk prediction score MRPS) which incorporated of these laboratory parameters in addition to physiological parameters has sensitivity of 82% and specificity of 75% with AUROC 0.79 value ≥ 2/18. Conclusions: The addition of laboratotory parameters to physiological variables improves performance of risk score to predict SAMO.